Seed microbiolization: a comparison with chemical treatment to control the main seed-borne pathogens of wheat - da Luz, Wilmar Cório (Pesquisa Agropecuaria Brasileira, 1998)
Results from ten experiments carried out in laboratory with microbiolization are compared with the chemical control iprodione + thiran as seed treatment against the following pathogens: Bipolaris sorokiniana (inducer of spot blotch, common root rot, and black point), Pyricularia oryzae (incitant of blast), Drechslera tritici-repentis (inducer of tan spot), and Stagonospora nodorum (incitant of glume blotch). In five experiments, seed microbiolization showed efficiency superior (five to nine per cent) to the fungicide treatment when the percentage of fungi on the seeds was evaluated (lots II, IV, V, VII, and VIII). In three experiments, the efficiency was equal (lots I, IX, and X). In two experiments, chemical seed treatment was more efficient (five to six per cent) than microbiologic treatment (lots III and VI). None of the treatments was specific to any pathogen. These results indicated that the biological method is a promising measure to protect seeds against the main wheat pathogens.
Keywords: biological control; Triticum aestivum; seed-borne fungi